Photon Strength Functions at the Low-Energy Tail of GEDR - Bečvář F. (EPJ Web of Conferences, 2010)
It is demonstrated that available experimental information on photon strength functions (PSFs) at energies below about 10 MeV is far from desired. Problems that occur during the extraction of PSFs from (n, γ), (γ,γ′), and 3He-induced reactions are discussed.